Adolescents with Cancer in Italy: Improving Access to National Cooperative Pediatric Oncology Group (AIEOP) Centers. Issue 6 (23rd February 2016) - Ferrari, Andrea; Rondelli, Roberto; Pession, Andrea; Mascarin, Maurizio; Buzzoni, Carlotta; Mosso, Maria Luisa; Maule, Milena; Barisone, Elena; Bertolotti, Marina; Clerici, Carlo Alfredo; Jankovic, Momcilo; Fagioli, Franca; et al.
Abstract : This analysis compared the numbers of patients treated at Italian pediatric oncology group (Associazione Italiana Ematologia Oncologia Pediatrica [AIEOP]) centers with the numbers of cases predicted according to the population‐based registry. It considered 32, 431 patients registered in the AIEOP database (1989–2012). The ratio of observed (O) to expected (E) cases was 0.79 for children (0–14 years old) and 0.15 for adolescents (15–19 years old). The proportion of adolescents increased significantly over the years, however, from 0.05 in the earliest period to 0.10, 0.18, and then 0.28 in the latest period of observation, suggesting a greater efficacy of local/national programs dedicated to adolescents.